Blockchain - Laurence, Tiana (For Dummies, 2023)
Carve out your niche in the exploding world of blockchain technology Cryptocurrency, NFTs, smart contracts, and ever-more-important business and finance functions--they all run on blockchain. Blockchain For Dummies is the must-have guide to the basics of blockchain. This clear reference breaks down exactly what blockchain technology is, how it's used across industries, and what it all means for you and your investment portfolio. Learn the latest token standards, emerging tools and platforms, and opportunities that you'll want to hop aboard. This book demystifies all of it, so you can understand and profit from this major disruptor in the world of finance. Evaluate new ideas and trends, make smarter decisions, and establish your presence on your blockchains of choice. Peek under the hood of the new tech that's changing finance (and everything else) Learn how blockchain powers cryptocurrency and smart contracts Launch your own blockchain apps on stable platforms Understand and take advantage of blockchain investment opportunities Investors, financial pros, and technologists who need Blockchain 101 will love Blockchain For Dummies. Exploring blockchain to build your personal portfolio? This book has your essentials.